2013
DOI: 10.5935/1808-8694.20130035
|View full text |Cite
|
Sign up to set email alerts
|

Use of inhaled versus oral steroids for acute dysphonia

Abstract: There was a significant improvement in the acute laryngitis concerning the assessments carried out in all the patients assessed, concerning the two treatments. The inhalation steroid treatment was significantly more effective in reducing the edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Hanania et al, 16 reported that these findings could be explained by the irritation of the laryngeal mucosa or by deposits from the inhalation of steroids. These results were similar to the findings of Souza et al, 17 who showed that voice pathology associated with ICS can cause increased noise components in the voice signal such as fundamental frequency, turbulent noise, and voice breaks. Roland et al, 18 in their study on the impact of ICS on voice, found an increased incidence of frequency and amplitude perturbation values (jitter and shimmer) in patients who received ICS in high doses and for a long duration.…”
Section: Discussionsupporting
confidence: 91%
“…Hanania et al, 16 reported that these findings could be explained by the irritation of the laryngeal mucosa or by deposits from the inhalation of steroids. These results were similar to the findings of Souza et al, 17 who showed that voice pathology associated with ICS can cause increased noise components in the voice signal such as fundamental frequency, turbulent noise, and voice breaks. Roland et al, 18 in their study on the impact of ICS on voice, found an increased incidence of frequency and amplitude perturbation values (jitter and shimmer) in patients who received ICS in high doses and for a long duration.…”
Section: Discussionsupporting
confidence: 91%
“…A prospective cohort study of 32 adult patients with acute dysphonia caused by laryngitis evaluated the effectiveness of treatment with inhaled fluticasone 50 mcg twice a day or oral prednisone 20 mg twice a day for seven days. 1 No control group was present in this study. Researcher excluded patients who smoked, had mental disorders, had physiological and motor problems, or had laryngeal structural disorders.…”
mentioning
confidence: 89%